Analisis Penggunaan Obat Rasional Dalam Peresepan Pada Kasus ISPA Non Pneumonia Di Rumah Sakit Umum Dr. Pirngadi Kota Medan - Hendrico H.P Simarmata; Sudiro -; Asriwati - (Jurnal Kesmas Prima Indonesia, 2021)
RSUD DR Pirngadi Medan has a large number of cases of non-pneumonia ARI in Medan city and found some irrational drug prescriptions by doctors. This study aims to analyze drugs by doctors in prescribing rational drug use in cases of ARI Non Pneumonia. This research is quantitative. The study took place from July-August 2020. The research population consisted of all general practitioners, pulmonary specialists, pediatricians and internal medicine specialists totaling 79 people. The survey data were analyzed using the Chi-Square test and linear regression. Based on the results of the study, it was found that there was a relationship between prescribing drugs by doctors based on correct diagnosis (p = 0.000), there was a relationship between prescribing drugs by doctors based on appropriate indications (p = 0.000), there was a relationship between prescribing drugs by doctors based on the exact type of drug (p = 0.000) , there is a relationship between prescribing drugs by doctors based on the right dose (p = 0.000), there is a relationship between prescribing drugs by doctors based on the correct assessment of the patient's condition (p = 0.000), there is a relationship between prescribing drugs by doctors based on accurate information (p = 0.000), there is a relationship prescribing drugs by doctors based on appropriate follow-up with rational drug use (p=0.000). The conclusion in this study is that all variables in this study are related to rational drug use in cases of ARI Non Pneumonia and the most dominant variable is the correct information variable. Research suggestions are to make improvements to patient records so that patient profiles are easier to see and therapeutic decisions are easier and more accurate